A novel RSA algorithm for secured key transmission in a centralized cloud environment. (8th January 2020) - Ambika, S.; Rajakumar, S.; Anakath, A.S.
Summary: Cloud computing has been gaining widespread significance in recent times, especially with the advent of state‐of‐the‐art communication technologies and data‐handling systems. Large volumes of data are being handled in real time and their availability is made feasible to consumers in an efficient manner through cloud computing networks. However, security of such data being transferred through clouds characterized in a centralized configuration is of prime concern, which has been investigated in this research paper. Secured transmission of data through a secured key transmission using appropriate authentication mechanism has been the driving force behind the research carried out in this paper. In order to resolve the existing issues in clouds in terms of computational as well as storage complexities, a secure key transmission Rivest‐Shamir‐Adleman (SKT‐RSA) protocol is proposed based on the secure key transmission. Key distribution between the certified authority and the end user is proposed. The proposed protocol is a tree‐based cluster key distribution scheme. Abstract : This proposed secure key transmission RSA (SKT‐RSA) protocol is based on the secure key transmission. Secured transmission of data through a secured key transmission using appropriate authentication mechanism has been the driving force behind this research work carried out in this paper. In order to resolve the existing issues in key distribution in distributed cloud environment in terms of computational as well as storage complexities, this SKT‐RSA protocol is proposed based on the secure key transmission. Key distribution between the certified authority and the end user is proposed. The proposed protocol is a tree‐based cluster key distribution scheme.